(untitled) (diségno, 2023)
The process of analyzing, interpreting, and configuring a landscape is based on a dual cognitive approach: a view from above, which provides an overall understanding of the phenomena taking place on the earth’s surface, and a view from the ground, focused on the physical experience of space, which require forms of representation more similar to perspective views. The experience of natural phenomena, such as flowering or foliage, is mainly based on the experiential approach at ground level but needs a broader view to establish analysis procedures able to support the design process, supported by cartographic representations showing the abstract point of view of the looking from above approach. The research was applied to the case study of the beech woodlands in the Lucanian Apennine Val d’Agri-Lagonegrese National Park, where it is possible to observe the phenomenon of the foliage of the woods with greater evidence, due to the homogeneity of these landscape areas. The methodology involves the use of dynamic mapping techniques which, through the processing of multispectral satellite images and the computing of vegetation indices, enable the features of the phenomenon to be represented in a spatio-temporal dimension. These forms of representation, on the one hand, can support decision-makers in defining territorial development strategies in the field of sustainable tourism, and on the other hand, they can be integrated into mobile web applications and/or web portals to provide geolocalized information which can be helpful for local actors and single users.